Resistência de Chenopodium quinoa “BRS Piabiru” à Heterodera glycines e Meloidogyne enterolobii - Gussi, Luis Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The use of alternative crops in succession and/or rotation, aiming to control nematodes, is essential for the sustainability of the areas and profitability of the agricultural activity. The objective of this work was to evaluate the resistance of Chenopodium quinoa “BRS Piabiru” to Heterodera glycines and Meloidogyne enterolobii. The experiment was conducted in completely randomized design methodology in a greenhouse with eight replications for each nematode species, in two planting times. The suspensions were properly prepared, containing 600 different development stages/mL, and 5 mL containing 3,000 nematodes per seedling were inoculated about seven days after quinoa emergence. Culture received all the necessary cultural treatments necessary for its development. To certify the viability of the inoculum, susceptibility standards were used, soybean was used for H. glycines and okra for M. enterolobii. It was observed that quinoa did not multiply Heterodera glycines and Meloidogyne enterolobii, being considered resistant, constituting an option to be used in succession and/or crop rotation in areas infested by the evaluated species.

A utilização de alternativas de culturas em sucessão e/ou rotação, visando o controle de nematoides, é fundamental para a sustentabilidade das áreas e rentabilidade da atividade agrícola. O objetivo do presente trabalho foi avaliar a resistência de Chenopodium quinoa “BRS Piabiru” à Heterodera glycines e Meloidogyne enterolobii. O experimento foi conduzido em delineamento inteiramente casualizado em casa de vegetação com oito repetições para cada espécie de nematoide, em duas épocas de plantio. As suspensões foram devidamente preparadas contendo 600 diferentes estádios de desenvolvimento / mL e inoculados 5 mL contendo 3.000 nematoides por plântula, cerca de sete dias após a emergência da quinoa. A cultura recebeu todos os devidos tratos culturais necessários para o seu desenvolvimento. Para atestar a viabilidade do inóculo foram utilizados padrões de sucetibilidade, sendo utilizada a soja para o H. glycines e o quiabeiro para o M. enterolobii. Foi observado que a quinoa não multiplicou Heterodera glycines e Meloidogyne enterolobii, sendo consideradas resistentes, constituindo opção a ser usada em sucessão e/ou rotação de culturas em áreas infestadas pelas espécies avaliadas.
Resitance of Chenopodium quinoa “BRS Piabiru” to Heterodera glycines and Meloidogyne enterolobii
Keywords: Alternative agriculture; Agricultura sustentável; Agricultura alternativa; Sistemas agrícolas; Quinoa